Spatial pattern of land use along the terrain gradient of Qinghai Tibet Plateau: a case study of Qiangtang Plateau, China - Bian, Kai; Tan, Lihua; Shen, Yulong; Chen, Xingtong; Xu, Jiahong (Frontiers in Environmental Science, 2023)
Understanding the land use and land cover (LULC) pattern of the Qinghai Tibet Plateau in China is crucial to support the structural and functional integrity of the ecological barrier of the plateau. This information has significant implications not only for the ecological environment and regional development of the plateau but also for the broader environmental impact at regional and global levels. It is critical to comprehend the spatial pattern and ascertain the underlying causes of land use and land cover in significant areas of the Qinghai Tibet Plateau. This can enable the formulation and implementation of context-specific policies and measures that can contribute to enhancing the ecological security barrier function of the plateau. This study focused on the core area of the Qinghai Tibet Plateau - the Qiangtang Plateau. Based on surface cover data from 2020 and ASTER GDEMV3 data, distribution indices and geographic detectors were used to explore the quantitative impact of land use/cover spatial patterns and terrain factors on land use/cover spatial distribution. The results showed the following: (1) The land use/cover space of the Qiangtang Plateau was dominated by grassland and bare land. Specifically, grassland had the greatest area, accounting for approximately 63.94% of the plateau area and covering an area of 449 983 km2. Grassland was widely distributed in most areas of the plateau. Bare land was the second-largest land cover type, with an area of 186 302 km2, accounting for 26.47% of the plateau area. Bare land was primarily located in the western and northern parts of the plateau. (2) The spatial differentiation of land use/cover in the Qiangtang Plateau was significant. Grasslands were primarily distributed in low mountainous areas characterized by high relief, gentle slopes, and low roughness. In contrast, bare land was mainly distributed in low mountainous areas with high relief, steep slopes, and low roughness. (3) The main drivers of the spatial distribution of land use/cover on the Qiangtang Plateau were elevation, roughness, and relief. Moreover, the interactions between these three terrain factors and other environmental variables significantly influenced the land use/cover pattern in the study area.